2021
DOI: 10.29271/jcpsp.2021.01.4
|View full text |Cite
|
Sign up to set email alerts
|

At What Age Threshold does the Decline in Semen Parameters Begin?

Abstract: Objective: To analyse changes in semen parameters according to different age groups in men presenting to an infertility clinic, and determine the age threshold for decline in semen quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Surprisingly, although nonshift workers were older and had a higher rate of smoking than shift workers in the present study, shift workers still had a lower semen quality. A recent study demonstrated a linear decrease in sperm motility, morphology and vitality as age advanced in infertile men (Demirkol et al, 2021). In another study, it was demonstrated that smoking had an independent negative effect on sperm concentration (De Brucker et al, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…Surprisingly, although nonshift workers were older and had a higher rate of smoking than shift workers in the present study, shift workers still had a lower semen quality. A recent study demonstrated a linear decrease in sperm motility, morphology and vitality as age advanced in infertile men (Demirkol et al, 2021). In another study, it was demonstrated that smoking had an independent negative effect on sperm concentration (De Brucker et al, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…A significant body of evidence consistently indicates a decrease in semen volume, motility, and the proportion of morphologically normal sperm with advancing age. Overall, the most consistent findings include APA's negative correlation with semen volume (7 of 9 studies) and motility (9 of 10 studies) as well as positive correlation with DNA fragmentation (11 of 11 studies) [4,[18][19][20]. Among others, a study involving 277 normozoospermic men revealed a significantly higher DNA Fragmentation Index (DFI) percentage in men older than 40 years compared to younger men [21].…”
Section: Introductionmentioning
confidence: 76%
“…It is important to know if older paternal age is associated with worse semen quality and an increased risk of infertility because more and more couples are seeking assistance from infertility clinics to establish babies later in life. Age was found to have a substantial impact on sperm volume, motility, and fast advancing motility [3] .…”
Section: Introductionmentioning
confidence: 93%